Cover Picture: Macromol. React. Eng. 3/2014. Issue 3 (March 2014) - Brusamarello, Claiton; Drenski, Michael F.; Isakov, Artem; Reed, Wayne F.
<x xml:space="preserve">Abstract</x> Cover: In this filtrodynamics study operating principles, produced prototype instrumentation, initial data, early models for interpreting data, and some intriguing correlations among filters, particle populations, and flow rates are established. Further details can be found in the article by C. Brusamarello, M. F. Drenski, A. Isakov, and W. F. Reed* on page 186. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>